2009
DOI: 10.1017/s0022149x09321173
|View full text |Cite
|
Sign up to set email alerts
|

Triclabendazole progress report, 2005–2009: an advancement of learning?

Abstract: Triclabendazole (TCBZ) remains the drug of choice for treating infections of the liver fluke, Fasciola hepatica in livestock and has become the main drug used to treat human cases of the disease as well. Cases of resistance in livestock continue to be reported, suggesting that the problem is increasing. In order to address the problem, there is a need for better understanding of drug action. A 'state-of-play' review on different aspects of TCBZ activity was published by the present author in 2005. The main pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
55
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(56 citation statements)
references
References 110 publications
(162 reference statements)
1
55
0
Order By: Relevance
“…The results of the present work showed that the drug efficacy on the hatchability of Fasciola eggs is increases drastically using silver nano particles combined with the drug of choice (10.33% and 30.33% respectively). Triclabendazole (TCBZ) is inhibiting of microtubule-dependent processes as a result of binding to the β-tubulin molecule [4547]. However, if TCBZ action is associated with microtubule depolymerisation, some egg damage would be expected considering that the drug may accumulate within the egg in therapeutic concentrations [48].…”
Section: Resultsmentioning
confidence: 99%
“…The results of the present work showed that the drug efficacy on the hatchability of Fasciola eggs is increases drastically using silver nano particles combined with the drug of choice (10.33% and 30.33% respectively). Triclabendazole (TCBZ) is inhibiting of microtubule-dependent processes as a result of binding to the β-tubulin molecule [4547]. However, if TCBZ action is associated with microtubule depolymerisation, some egg damage would be expected considering that the drug may accumulate within the egg in therapeutic concentrations [48].…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, the number of F . hepatica infections has dramatically risen, a trend that has been attributed to climate change [4,5]. The prevalence of fasciolosis has increased by up to 12-fold in the EU member states during recent years [6].…”
Section: Introductionmentioning
confidence: 99%
“…Currently the treatment of fascioliasis in humans relies on one single drug, triclabendazole. Though triclabendazole resistance has not been shown in humans, resistance to this drug is widely spreading in sheep and cattle [8,9]. In veterinary medicine additional drugs are commonly used in the treatment of infections with Fasciola spp.…”
Section: Introductionmentioning
confidence: 99%